Coating film, coating film-forming composition, and coated article

JP2025025896APending Publication Date: 2025-02-21NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023131115
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

Smart Images

  • Figure 2025025896000004
    Figure 2025025896000004
  • Figure 2025025896000001
    Figure 2025025896000001
  • Figure 2025025896000002
    Figure 2025025896000002
Patent Text Reader

Abstract

To provide a coating film that offers excellent ease of cleaning against stubborn dirt, a coating film-forming composition for forming the coating film, and a coated article provided with the coating film.SOLUTION: The present invention provides a coating film containing (A) a resin, wherein the (A) resin has at least two functional groups on its side chains, and the surface of the coating film has a water contact angle of 65° or less and a water sliding angle of 60° or less. The present invention also provides a coating film-forming composition for forming the coating film, wherein the composition contains (a) a resin component, wherein the (a) resin component contains at least two resins with different functional groups.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating film, a coating-forming composition, and an article with a coating film. [Background technology]

[0002] 2. Description of the Related Art Conventionally, in order to prevent adhesion of dirt and scratches on structures, a method of protecting the surfaces of structures and structural members with an antifouling coating film has been used.

[0003] It is desirable for structures and structural components that require anti-fouling properties to be able to remove dirt by a simple method, and research is currently being conducted into coating films that have self-cleaning properties that allow adhering dirt to be washed away by rainfall, etc.

[0004] For example, Patent Document 1 describes an antifouling coating composition that swells when in contact with water, thereby exhibiting excellent antifouling properties over a long period of time, and does not release harmful substances into the water because there is no need for the coating film itself to dissolve or for the addition of chemicals, making it particularly useful for drainage channels and the like. Furthermore, Patent Document 2 discloses a paint coating film that is imparted with hydrophilicity and thus exhibits self-cleaning properties when exposed to the outdoors, thereby providing long-term stain resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2021-84924 Summary of the Invention [Problem to be solved by the invention]

[0006] In the above Patent Documents 1 and 2, the performance of removing adhered dirt by a simple method such as washing with running water is not sufficient.

[0007] The present invention aims to provide a coating film-forming composition that can provide a coating film from which adhering dirt such as soot can be easily removed, i.e., a coating film that is excellent in cleanability, a coating film made of the composition, and an article with the coating film. [Means for solving the problem]

[0008] As a result of intensive research to solve the above problems, the inventors of the present application have discovered that a coating film that is easy to clean against adhered dirt can be obtained by containing an (A) resin having at least two types of functional groups in its side chain, and by making the contact angle with water equal to or less than a predetermined value and the sliding angle of water equal to or less than a predetermined value, and have thus completed the present invention.

[0009] That is, the object of the present invention can be achieved as follows. [1] (A) A coating film containing a resin, The (A) resin has at least two types of functional groups in its side chain, The coating film has a surface having a contact angle with water of 65° or less and a sliding angle of water of 60° or less. [2] The coating film according to [1], wherein the (A) resin has a crosslinked structure. [3] The coating film according to [1] or [2], wherein the functional groups of the (A) resin include a hydrophobic functional group and a hydrophilic functional group. [4] The coating film according to [3], wherein the content of the structural unit (a2-1) containing a hydrophobic functional group in the resin (A) is 10% by mass to 50% by mass. [5] The coating film according to [3], wherein the content of the structural unit (a1-1) containing a hydrophilic functional group in the resin (A) is 6% by mass to 50% by mass. [6] The coating film according to [3], wherein the hydrophobic functional group is at least one selected from a fluoro group, a fluorinated alkyl group, an alkyl group, and an alkylsilyl group. [7] The coating film according to [3], wherein the hydrophilic functional group is at least one selected from an alkoxy group, a hydroxy group, an amine group, a sulfone group, an amino group, an amide group, an imino group, a mercapto group, a hydrazino group, a carboxyl group, a sulfate ester group, a phosphate ester group, and a quaternary ammonium group. [8] A coating film-forming composition for forming the coating film according to [1], (a) containing a resin component, The (a) resin component is a coating forming composition containing at least two kinds of resins each having a different functional group. [9] The coating forming composition according to [8], wherein the (a) resin component comprises a resin (a1) having a hydrophilic functional group in a side chain and a resin (a2) having a hydrophobic functional group in a side chain.

[10] The coating forming composition according to [9], wherein the resin (a1) and the resin (a2) are acrylic resins.

[11] The coating forming composition according to any one of [8] to

[10] , further comprising (b) a crosslinking agent.

[12] An article having the coating film according to [1] or [2]. Effect of the Invention

[0010] The present invention can provide a coating film that is excellent in ease of cleaning adhered dirt, a coating film-forming composition that forms the coating film, and an article with the coating film. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view showing an article having a coating film formed thereon, the coating film being made of a coating film-forming composition according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified in any manner without departing from the gist of the present invention. In this specification, the term "A to B" indicating a range means "greater than or equal to A and less than or equal to B." Furthermore, in this specification, "weight" and "mass," "weight %" and "mass %" are treated as synonyms.

[0013] Hereinafter, the embodiments for carrying out the present invention will be described in detail. Note that the present invention is not limited to the embodiments described below. In addition, in the following drawings, members and parts having the same function may be described with the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments shown in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the actual product.

[0014] Fig. 1 is a cross-sectional view showing an article with a coating film according to an embodiment of the present invention formed on an adherend. As shown in Fig. 1, a coating film forming composition according to an embodiment of the present invention is applied to the surface of an adherend 31, and then dried to form a coating film 21 according to an embodiment of the present invention.

[0015] The coating film and the coating-forming composition according to the embodiment of the present invention will be described in detail below.

[0016] <Coating film> The coating film according to an embodiment of the present invention is a coating film containing a resin (A), The (A) resin has at least two types of functional groups in its side chain, The coating surface has a contact angle with water of 65° or less and a sliding angle of water of 60° or less. The coating film according to the embodiment of the present invention is a coating film having an excellent surface cleanability.

[0017] The water contact angle and water sliding angle of the coating film according to the embodiment of the present invention are values ​​measured using any one of the measurement coating film samples 1 to 4 prepared by the following method. Hereinafter, the contact angle of the coating surface with water will be simply referred to as the "contact angle," and the sliding angle of water will be simply referred to as the "sliding angle."

[0018] [Contact angle and sliding angle of coating film sample for measurement] Method for preparing coating film sample 1 for measurement: A coating film-forming composition for forming the coating film was applied to the surface of a PET film having a thickness of 75 μm so that the wet thickness was 200 μm, and the film was heated at 80° C. for 1 minute to form a layer. A release sheet was attached to the surface of the layer, and the release sheet side was exposed to an illuminance of 2.5 mW / cm 2 The coating film is cut out to an area of ​​10 mm x 100 mm, and the release sheet is peeled off to prepare coating film sample 1 for measurement.

[0019] Method for preparing coating film sample 2 for measurement: A coating film-forming composition for forming the coating film was applied to the surface of a PET film having a thickness of 75 μm so that the wet thickness was 200 μm, and the film was heated at 80° C. for 1 hour to form a layer on which a release sheet was attached, and the surface on the release sheet side was exposed to an illuminance of 2.5 mW / cm 2 The coating is then cut out to an area of ​​10 mm x 100 mm, and the release sheet is peeled off to prepare coating sample 2 for measurement.

[0020] Method for preparing coating film sample 3 for measurement: A coating film-forming composition for forming the coating film was applied to the surface of a PET film having a thickness of 75 μm so that the wet thickness was 200 μm, and the film was heated at 80° C. for 1 hour to form a layer on which a release sheet was attached, and the surface on the release sheet side was exposed to an illuminance of 2.5 mW / cm 2 The coating film is cut out to an area of ​​10 mm x 100 mm, and the release sheet is peeled off to prepare coating film sample 3 for measurement.

[0021] Method for preparing coating sample 4 for measurement: A coating composition for forming the coating is applied to the surface of a PET film having a thickness of 75 μm so that the wet thickness is 200 μm, and the film is heated at 80° C. for 1 hour to prepare coating sample 4 for measurement.

[0022] Here, the wet thickness is the film thickness immediately after application.

[0023] The contact angle is measured by dropping 2 μL of water onto the coating surface of the measurement coating sample, and measuring the contact angle of the coating surface after 5 minutes using a contact angle meter (e.g., DropMaster, DM-701, manufactured by Kyowa Interface Science Co., Ltd.) according to the sessile drop method according to JIS R 3257.

[0024] More specifically, in the coating forming composition according to the embodiment of the present invention, in an aspect in which the cleaning property against the adhesion dirt is particularly excellent, the contact angle may be 65° or less, or 60° or less. Also, it may be 20° or more, 30° or more, 40° or more, or 45° or more. When the contact angle is in the above range, the cleaning property with running water is excellent.

[0025] The sliding angle is measured by dropping 20 μL of water onto the coating surface of the measurement coating sample, and measuring the angle (°) traveled by the water droplet by tilting the sliding angle of the coating surface by 1° per second using a contact angle meter (e.g., DropMaster, DMo-501, manufactured by Kyowa Interface Science Co., Ltd., etc.) using a dynamic sliding method.

[0026] More specifically, in the coating forming composition according to the embodiment of the present invention, in an aspect in which the cleaning property against stuck dirt is particularly excellent, the sliding angle may be, for example, 60° or less, 50° or less, or 40° or less. It may also be 10° or more, 20° or more, or 30° or more. When the sliding angle is in the above range, the cleaning property with running water is excellent.

[0027] [(A) Resin] The coating film according to the embodiment of the present invention contains a resin (A) having at least two types of functional groups in the side chain. The resin (A) is not particularly limited as long as it has at least two types of functional groups in the side chain, and various resins can be used. As described later, when forming a coating film as a coating film-forming composition, a resin that satisfies a predetermined contact angle and sliding angle can be appropriately selected and used.

[0028] Examples of the (A) resin include polyurethane resins, acrylic resins, polystyrene resins, rubber resins, silicone resins, vinyl alkyl ether resins, polyvinyl alcohol resins, polyvinylpyrrolidone resins, polyacrylamide resins, cellulose resins, polyester resins, fluorine resins, etc. Among these, at least one selected from acrylic resins, polyurethane resins, polystyrene resins, and rubber resins is preferred, and acrylic resins are more preferred.

[0029] Examples of the functional group contained in the (A) resin include a hydrophilic functional group and a hydrophobic functional group, and it is preferable that the resin contains a hydrophilic functional group and a hydrophobic functional group. When the (A) resin contains a hydrophilic functional group and a hydrophobic functional group as at least two types of functional groups in a side chain, the (A) resin is preferably a resin having a structural unit containing a hydrophobic functional group and a structural unit containing a hydrophilic functional group.

[0030] Examples of hydrophilic functional groups include alkoxy groups such as methoxy and ethoxy groups, hydroxy groups, amine groups, sulfone groups, amino groups, amide groups, imino groups, mercapto groups, hydrazino groups, carboxyl groups, sulfate ester groups, phosphate ester groups, and quaternary ammonium groups. Preferred are alkoxy groups such as methoxy and ethoxy groups, hydroxy groups, and quaternary ammonium groups, and more preferred are quaternary ammonium groups.

[0031] (A) Resin contains hydrophilic functional groups, which increases the hydrophilicity of the coating film, and when the coating film gets wet (comes into contact with) water during washing with water, it has the effect of lifting off dirt that has adhered to the surface.

[0032] In the coating film according to the embodiment of the present invention, when the (A) resin contains a hydrophilic functional group, from the viewpoint of the film-forming property of the coating film and the ease of cleaning with running water, the content of the structural unit (a1-1) containing a hydrophilic functional group in the (A) resin is preferably 6% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. Also, it is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less, and even more preferably 30% by mass or less.

[0033] Examples of the hydrophobic functional group include a fluoro group, a fluorinated alkyl group, an alkyl group, and an alkylsilyl group.

[0034] The (A) resin contains a hydrophobic functional group, which has a water-repellent effect, thereby enabling the expulsion of water that has penetrated into the coating film and preventing liquid from remaining on the coating film surface.

[0035] In the coating film according to the embodiment of the present invention, when the (A) resin contains a hydrophobic functional group, from the viewpoint of the film-forming property of the coating film and the ease of cleaning with running water, the content of the structural unit (a2-1) containing a hydrophobic functional group in the (A) resin is preferably 10% by mass or more, more preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. Also, it is preferably 50% by mass or less, and more preferably 40% by mass or less.

[0036] The (A) resin contained in the coating film according to the embodiment of the present invention may have a crosslinked structure, which has the advantages of improving film-forming properties and water resistance.

[0037] The crosslinking agent for forming a crosslinked structure of the (A) resin is not particularly limited, and examples thereof include the crosslinking agents described below.

[0038] In the (A) resin contained in the coating film according to the embodiment of the present invention, the above-mentioned hydrophilic functional group, hydrophobic functional group, crosslinked structure, etc. are 1 H-NMR, 13 This can be confirmed by NMR analysis such as C-NMR, pyrolysis GC / MS analysis, infrared spectroscopy (for example, FTIR method), etc. The content of the above-mentioned structural units in the acrylic polymer can usually also be calculated from the blending amount (charge amount) when forming the (A) resin.

[0039] The thickness of the coating film may be any appropriate thickness depending on the application and the environment of use. The thickness of the coating film is preferably 50 μm to 1000 μm, more preferably 80 μm to 500 μm. If the thickness of the coating film is 50 μm or more, the effect of protecting the adherend can be sufficiently obtained. Also, if the thickness of the coating film is 1000 μm or less, the work efficiency when forming the coating film is excellent. The thickness of the coating film can be measured, for example, using RI-205 manufactured by PEAKOCK.

[0040] The coating film according to the embodiment of the present invention can be formed by the coating film-forming composition according to the embodiment of the present invention described later. For example, the coating film can be formed by applying the coating film-forming composition to the surface of the adherend and drying it. The method for forming the coating film will also be described in detail later.

[0041] The coating film according to the embodiment of the present invention may be composed of only a coating film. The coating film-forming composition applied to a substrate may be formed into a coating film by, for example, drying, and the formed coating film may be protected by, for example, a release sheet.

[0042] The coating film is not particularly limited, but may be, for example, at least one selected from a coating layer, a printed layer, a vapor deposition layer, a sputtered layer, an atomic layer deposition (ALD) layer, a CVD (chemical vapor deposition) layer, a spin-coated layer, a dip-coated layer, an alternating laminate layer, a Langmuir-Blodgett layer, and a plating layer.

[0043] The composition can be applied directly to any substrate by any known application method such as spraying, brushing, roller, curtain flow, roll, dip, or coater.

[0044] <Composition for coating film formation> The coating film-forming composition according to an embodiment of the present invention is a coating film-forming composition containing (a) a resin component, (a) the resin component contains at least two types of resins each having a different functional group; The coating composition has a contact angle of 65° or less and a sliding angle of 60° or less in a coating sample for measurement prepared by the method described below. Method for preparing a coating sample for measurement: The coating composition was applied to the surface of a PET film having a thickness of 75 μm so that the wet thickness was 200 μm, and the film was heated at 80° C. for 1 hour to form a layer. A release sheet was attached to the surface of the layer, and the release sheet was exposed to an illuminance of 2.5 mW / cm 2 The coating is then cut out to an area of ​​10 mm x 100 mm, and the release sheet is peeled off to prepare a coating sample for measurement.

[0045] The coating film according to the embodiment of the present invention may be formed from the coating film-forming composition according to the embodiment of the present invention. That is, a coating film containing the above-mentioned (A) resin can be formed by using a coating film-forming composition containing the above-mentioned (a) resin component.

[0046] The coating film forming composition according to the embodiment of the present invention can form a coating film with excellent cleaning properties. Although the mechanism of action is unclear, it is presumed that the coating film contains the resin component (a) containing at least two types of resins each having different functional groups, which changes the surface state of the coating film, thereby improving the ability to remove stuck dirt with running water. However, the present invention is not limited to this mechanism of action.

[0047] [Contact angle and sliding angle of coating film sample for measurement] The coating forming composition according to the embodiment of the present invention has a contact angle of 65° or less and a sliding angle of 60° or less in a coating measurement sample prepared by the following method. Method for preparing a coating sample for measurement: The coating composition was applied to the surface of a PET film having a thickness of 75 μm so that the wet thickness was 200 μm, and the film was heated at 80° C. for 1 hour to form a layer. A release sheet was attached to the surface of the layer, and the release sheet was exposed to an illuminance of 2.5 mW / cm 2 The coating is then cut out to an area of ​​10 mm x 100 mm, and the release sheet is peeled off to prepare a coating sample for measurement. Here, the wet thickness is the film thickness immediately after application.

[0048] The method for measuring the contact angle and sliding angle and the preferred ranges thereof are the same as those for the contact angle and sliding angle of the coating film sample for measurement of the coating film according to the embodiment of the present invention described above, and the preferred ranges are also the same.

[0049] Each component contained in the coating film-forming composition will be described in more detail below.

[0050] <(a) Resin component> In the coating forming composition according to the embodiment of the present invention, the (a) resin component contains at least two types of resins each having a different functional group. In the coating forming composition according to the embodiment of the present invention, the (a) resin component preferably contains, as two types of resins each having a different functional group, a resin (a1) having a hydrophilic functional group at a side chain (hydrophilic resin (a1)) and a resin (a2) having a hydrophobic functional group at a side chain (hydrophobic resin (a2)).

[0051] As the hydrophilic resin (a1) and the hydrophobic resin (a2), various resins can be used, and as described below, resins can be appropriately selected so that the coating film formed from the coating film-forming composition satisfies the specified contact angle and sliding angle.

[0052] Examples of the hydrophilic resin (a1) and the hydrophobic resin (a2) include polyurethane resins, acrylic resins, polystyrene resins, rubber resins, silicone resins, vinyl alkyl ether resins, polyvinyl alcohol resins, polyvinylpyrrolidone resins, polyacrylamide resins, cellulose resins, polyester resins, fluorine resins, etc. At least one selected from acrylic resins, polyurethane resins, polystyrene resins, and rubber resins is preferred, and acrylic resins are more preferred.

[0053] The polyurethane resin is typically a reaction product of a polyol and a polyisocyanate. As the polyol component, a polymer polyol such as a polycarbonate polyol, a polyacrylic polyol, a polyester polyol, or a polyether polyol is preferably used.

[0054] Representative examples of polycarbonate polyols include reaction products of polyhydric alcohols with phosgene, chloroformate, dialkyl carbonates, or diaryl carbonates; ring-opening polymers of cyclic carbonates (alkylene carbonates, etc.). Specifically, in the reaction products of polyhydric alcohols with phosgene, examples of the polyhydric alcohols that can be used include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol. In addition, examples of the alkylene carbonates in the ring-opening polymers of cyclic carbonates include ethylene carbonate, trimethylene carbonate, tetramethylene carbonate, and hexamethylene carbonate. The polycarbonate polyol may be any compound having a carbonate bond in the molecule and a hydroxyl group at the end, and may have an ester bond in addition to the carbonate bond.

[0055] Polyacrylic polyol is typically obtained by polymerization of (meth)acrylic acid ester and hydroxyl group-containing monomer. Examples of (meth)acrylic acid ester include methyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. Examples of hydroxyl group-containing monomer include hydroxyalkyl ester of (meth)acrylic acid such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxypentyl (meth)acrylate, etc.; (meth)acrylic acid monoester of polyhydric alcohol such as glycerin and trimethylolpropane; N-methylol (meth)acrylamide, etc.

[0056] The polyester polyol is typically obtained by the reaction of a polybasic acid with a polyol. Examples of the polybasic acid include aromatic dicarboxylic acids such as orthophthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyldicarboxylic acid, and tetrahydrophthalic acid; aliphatic dicarboxylic acids such as oxalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, dodecanedicarboxylic acid, octadecanedicarboxylic acid, tartaric acid, alkyl succinic acid, linoleic acid, maleic acid, fumaric acid, mesaconic acid, citraconic acid, and itaconic acid; alicyclic dicarboxylic acids such as hexahydrophthalic acid, tetrahydrophthalic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid; and reactive derivatives thereof such as acid anhydrides, alkyl esters, and acid halides.

[0057] Polyether polyols are typically obtained by adding alkylene oxides to polyhydric alcohols through ring-opening polymerization. Examples of polyhydric alcohols include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, glycerin, trimethylolpropane, etc. Examples of alkylene oxides include ethylene oxide, propylene oxide, butylene oxide, styrene oxide, tetrahydrofuran, etc.

[0058] Examples of polyisocyanates include aromatic, aliphatic, and alicyclic diisocyanates, as well as dimers and trimers of these diisocyanates. Examples of aromatic, aliphatic, and alicyclic diisocyanates include tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI), naphthylene diisocyanate (NDI), phenylene diisocyanate (PPDI), m-tetramethylxylylene diisocyanate (TMXDI), methylcyclohexane diisocyanate (hydrogenated TDI), dicyclohexylmethane diisocyanate (PPDI), and methylcyclohexane diisocyanate (TDI). Examples of the isocyanate include bis(isocyanatomethyl)cyclohexane (hydrogenated XDI), norbornene diisocyanate (NBDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), butane diisocyanate, 2,4-trimethylhexamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate. Dimers and trimers of these and polyphenylmethane diisocyanate are also used. Examples of trimers include isocyanurate type, biuret type, and allophanate type, and can be used as appropriate.

[0059] Among these, aliphatic and alicyclic diisocyanates such as methylcyclohexane diisocyanate (hydrogenated TDI), dicyclohexylmethane diisocyanate (hydrogenated MDI), cyclohexane diisocyanate (hydrogenated PPDI), bis(isocyanatomethyl)cyclohexane (hydrogenated XDI), norbornene diisocyanate (NBDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), hydrogenated 4,4-diphenylmethane diisocyanate (HMDI), butane diisocyanate, 2,4-trimethylhexamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate are particularly preferably used.

[0060] These polyisocyanates can be used alone or in combination. The type and combination of polyisocyanates can be appropriately selected from the viewpoints of the characteristics of the adherend, solubility, reactivity with hydroxyl groups, etc.

[0061] As the polyisocyanate, it is preferable to use at least one diisocyanate selected from the group consisting of hexamethylene diisocyanate (HDI), hydrogenated tolylene diisocyanate (HTDI), hydrogenated 4,4-diphenylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), and hydrogenated xylene diisocyanate (HXDI), and hydrogenated 4,4-diphenylmethane diisocyanate (HMDI) is particularly preferable.

[0062] The acrylic resin is preferably one obtained by emulsion polymerization of an acrylic monomer component containing an alkyl (meth)acrylate, for example.

[0063] Examples of alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate. These alkyl (meth)acrylates can be used alone or in combination of two or more. Among them, preferred alkyl (meth)acrylates include n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA).

[0064] In this specification, "(meth)acrylic" means acrylic and / or methacrylic. Acrylic resins include those containing acrylic acid or a derivative thereof as a constituent monomer component, and those containing methacrylic acid or a derivative thereof as a constituent monomer component.

[0065] The proportion of alkyl (meth)acrylate in all monomer components used in the synthesis of the acrylic resin is preferably 70% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more. The upper limit of the proportion of the alkyl (meth)acrylate is not particularly limited, but it is usually preferably 99.5% by mass or less (for example, 99% by mass or less).

[0066] Examples of polystyrene-based resins that can be used include SBS (styrene-butadiene block copolymer), SIS (styrene-isoprene block copolymer), SEBS (styrene-ethylene-butylene-styrene block copolymer), SEPS (styrene-ethylene-propylene-styrene block copolymer), and SEEPS (styrene-ethylene-ethylene-propylene-styrene block copolymer).

[0067] Examples of the rubber-based resin include acrylic rubber, diene rubber, butyl rubber, nitrile rubber, hydrogenated nitrile rubber, fluororubber, silicone rubber, ethylene propylene rubber, chloroprene rubber, urethane rubber, and epichlorohydrin rubber, and it is particularly preferable to use acrylic rubber, diene rubber, and urethane rubber. Examples of the diene-based rubber include natural rubber, isoprene rubber, butadiene rubber, styrene butadiene rubber, chloroprene rubber, and acrylonitrile butadiene rubber, and it is preferable to use styrene butadiene rubber.

[0068] (Hydrophilic resin (a1)) The hydrophilic resin (a1) preferably contains a structural unit (a1-1) having a hydrophilic functional group in a side chain, and may further contain a structural unit (a1-2) having a reactive group in a side chain. For example, when the hydrophilic resin (a1) is an acrylic resin, the structural units other than the structural unit (a1-1) and the structural unit (a1-2) may be derived from an acrylic monomer.

[0069] Examples of hydrophilic functional groups include alkoxy groups such as methoxy and ethoxy groups, hydroxy groups, amine groups, sulfone groups, amino groups, amide groups, imino groups, mercapto groups, hydrazino groups, carboxyl groups, sulfate ester groups, phosphate ester groups, and quaternary ammonium groups. Preferred are alkoxy groups such as methoxy and ethoxy groups, hydroxy groups, and quaternary ammonium groups, and more preferred are quaternary ammonium groups.

[0070] The hydrophilic resin (a1) is preferably, for example, a modified acrylic resin containing a quaternary ammonium group. Commercially available products of such hydrophilic resin (a1) include the "1WX" (registered trademark) series, the "8WX" (registered trademark) series, and the "3WX" (registered trademark) series manufactured by Taisei Fine Chemical Co., Ltd.

[0071] In the coating forming composition according to the embodiment of the present invention, the content of the structural unit (a1-1) containing a hydrophilic functional group in the (a) resin component is preferably 6% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less, and even more preferably 30% by mass or less.

[0072] The content of the hydrophilic resin (a1) contained in the coating forming composition according to the embodiment of the present invention is not particularly limited, but from the viewpoints of film-forming properties and ease of cleaning with running water, it is preferably 1 to 50 mass % and more preferably 30 to 50 mass % in the (a) resin component.

[0073] (Hydrophobic resin (a2)) The hydrophobic resin (a2) preferably contains a structural unit (a2-1) having a hydrophobic functional group in a side chain, and may further contain a structural unit (a2-2) having a reactive functional group in a side chain. For example, when the hydrophobic resin (a2) is an acrylic resin, the structural units other than the structural unit (a2-1) and the structural unit (a2-2) may be derived from an acrylic monomer.

[0074] Examples of the hydrophobic functional group include a fluoro group, a fluorinated alkyl group, an alkyl group, and an alkylsilyl group.

[0075] Examples of the reactive functional group include a hydroxyl group and a vinyl group.

[0076] The hydrophobic resin (a2) is preferably, for example, a silicon-modified acrylic resin. Examples of commercially available products of such hydrophobic resin (a2) include UV-curable silicone-fluorinated acrylic polymers, 8FS series (e.g., 8FS-001, 8FS-009, etc.), manufactured by Taisei Fine Chemical Co., Ltd., and silicon-modified acrylic polymers, 8BS series, manufactured by Taisei Fine Chemical Co., Ltd.

[0077] Furthermore, in the coating forming composition according to an embodiment of the present invention, from the viewpoints of film-forming ability and ease of cleaning with running water, the content of the structural unit (a2-1) containing a hydrophobic functional group in the resin component (a) is preferably 10 mass % or more, more preferably 15 mass % or more, even more preferably 20 mass % or more, even more preferably 25 mass % or more, and is preferably 50 mass % or less, and more preferably 40 mass % or less.

[0078] The content of the hydrophobic resin (a2) contained in the coating forming composition according to the embodiment of the present invention is not particularly limited, but is preferably 50 to 70 mass %, more preferably 50 to 60 mass %, in the (a) resin component.

[0079] The coating forming composition of the present invention may contain other components as necessary within the scope of the object of the present invention. Each component of the composition will be described below.

[0080] [Crosslinking Agent] The coating composition according to the embodiment of the present invention preferably further contains a crosslinking agent. The crosslinking agent promotes the crosslinking reaction of the resin (a) and contributes to the formation of a crosslinked structure inside the coating film. In this case, the crosslinking agent may or may not be incorporated into the crosslinked structure.

[0081] Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, silicone-based crosslinking agents, silane-based crosslinking agents, etc. Among these, isocyanate-based crosslinking agents are preferred as the crosslinking agent from the viewpoint of excellent reactivity and handling.

[0082] Examples of the isocyanate-based crosslinking agent include polyfunctional isocyanates and isocyanate-containing acrylic compounds.

[0083] A preferred polyfunctional isocyanate is one having an average of three or more isocyanate groups per molecule. Such a trifunctional or higher isocyanate may be a multimer (typically a dimer or trimer) of a bifunctional or trifunctional or higher isocyanate, a derivative (for example, an addition reaction product of a polyhydric alcohol and two or more molecules of a polyfunctional isocyanate), a polymer, etc. For example, a dimer or trimer of diphenylmethane diisocyanate, an isocyanurate of hexamethylene diisocyanate (a trimer adduct of an isocyanurate structure), a reaction product of trimethylolpropane and tolylene diisocyanate, a reaction product of trimethylolpropane and hexamethylene diisocyanate, polymethylene polyphenyl isocyanate, polyether polyisocyanate, polyester polyisocyanate, and other polyfunctional isocyanates may be mentioned. Commercially available examples of such polyfunctional isocyanates include those manufactured by Asahi Kasei Chemicals Corporation under the trade names "Duranate TPA-100," and those manufactured by Tosoh Corporation under the trade names "Coronate L," "Coronate HL," "Coronate HK," "Coronate HX," "Coronate HXR," and "Coronate 2096."

[0084] Examples of the isocyanate-containing acrylic compound include isocyanatoalkyl(meth)acrylate and (meth)acryloyl(poly)oxyalkylenealkylisocyanate. The isocyanate-containing acrylic compound can be used alone or in combination.

[0085] Examples of the isocyanatoalkyl(meth)acrylate include isocyanatoalkyl(meth)acrylates having an alkyl group with 1 to 4 carbon atoms, and specific examples thereof include isocyanatomethyl(meth)acrylate, isocyanatoethyl(meth)acrylate, isocyanatopropyl(meth)acrylate, and isocyanatobutyl(meth)acrylate.

[0086] Examples of the (meth)acryloyl(poly)oxyalkylene alkyl isocyanate include (meth)acryloylpolyoxyethylene ethyl isocyanate and (meth)acryloyloxyethyloxyethyl isocyanate.

[0087] As the isocyanate-containing acrylic compound, preferably, isoanatoalkyl(meth)acrylate is used, more preferably, isoanatoethyl(meth)acrylate is used, and further preferably, 2-isoanatoethyl acrylate is used.

[0088] Such an isocyanate-containing acrylic compound may be a commercially available product, and examples of such commercially available products include Karenz AOI (manufactured by Showa Denko K.K., 2-isoanatoethyl acrylate), Karenz MOI (manufactured by Showa Denko K.K., 2-isoanatoethyl methacrylate) and Karenz MOI-EG (manufactured by Showa Denko K.K., 2-(2-methacryloyloxyethyloxy)ethyl isocyanate), preferably Karenz MOI (manufactured by Showa Denko K.K., 2-isoanatoethyl methacrylate).

[0089] In the coating forming composition according to the embodiment of the present invention, the amount of the crosslinking agent is, from the viewpoint of film-forming property, for example, 0.01 parts by mass or more, preferably 0.05 parts by mass or more, and more preferably 1 part by mass or more, relative to 100 parts by mass of the (a) resin component. From the viewpoint of film-forming property, the amount of the crosslinking agent is, for example, 100 parts by mass or less, preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, relative to 100 parts by mass of the (a) resin component.

[0090] [Polymerization initiator] The coating film-forming composition according to the embodiment of the present invention preferably further contains a polymerization initiator. The polymerization initiator contributes to crosslinking and film-forming properties of the coating film, and ease of cleaning with running water. Examples of the polymerization initiator used in the embodiment of the present invention include a thermal polymerization initiator, a heat polymerization initiator, and a photopolymerization initiator.

[0091] Examples of the thermal polymerization initiator include azo polymerization initiators and peroxide polymerization initiators. Examples of the azo polymerization initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionate) dimethyl, 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2-methylpropionamidine) disulfate, and 2,2'-azobis(N,N'-dimethyleneisobutylamidine) dihydrochloride. Peroxide polymerization initiators include, for example, dibenzoyl peroxide, t-butyl permaleate, and lauroyl peroxide.

[0092] Examples of the photopolymerization initiator include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and acylphosphine oxide-based photopolymerization initiators.

[0093] The amount of the polymerization initiator used is, relative to 100 parts by mass of the (a) resin component, for example, 0.05 parts by mass or more, preferably 0.08 parts by mass or more, and for example, 1 part by mass or less, preferably 0.5 parts by mass or less.

[0094] 〔solvent〕 The coating forming composition according to the embodiment of the present invention may further contain a solvent. Examples of the solvent used in the embodiment of the present invention include aromatic hydrocarbons such as toluene, xylene, and Solvesso; esters such as methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, amyl acetate, ethyl formate, methyl propionate, ethyl propionate, butyl propionate, methoxypropyl acetate, and 2-ethoxyethyl acetate; alcohols such as methanol, ethanol, 1-propanol, isopropyl alcohol, 1-butanol, 2-ethylhexanol, ethylene glycol, methoxypropanol, 2-ethoxyethanol, and 2-butoxyethanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as diethyl ether, ethylene glycol dimethyl ether, tetrahydrofuran, and dioxane. These solvents can be used alone or in combination of two or more. There is no particular limit to the amount of solvent used, but from the viewpoint of coatability and solubility or dispersibility of materials, it is preferable to use the solvent so that the solid content in the coating film forming composition according to the embodiment of the present invention is 20 to 70 mass %.

[0095] (Other ingredients)

[0096] The coating composition may contain any other suitable additives within the scope of not impairing the effects of the present invention, such as crosslinking accelerators, ultraviolet absorbers, light stabilizers, antioxidants, antiaging agents, antistatic agents, pigments, dyes, leveling agents, thickeners, etc.

[0097] The coating forming composition according to the embodiment of the present invention can be obtained by mixing the components and heating and stirring as necessary. The heating temperature is, for example, 30° C. or more and 90° C. or less, and preferably 70° C. or less. The heating time is, for example, 30 minutes or more and 10 hours or less, and preferably 5 hours or less.

[0098] The coating film-forming composition according to the embodiment of the present invention can be applied to an adherend and dried to form a coating film.

[0099] The coating film-forming composition according to the embodiment of the present invention may be prepared by reacting each component contained in the coating film-forming composition in part or in whole, and then applying the coating film-forming composition or a solution thereof to an adherend and drying it. Also, the coating film-forming composition according to the embodiment of the present invention may be prepared by applying the coating film-forming composition or a solution thereof to an adherend and drying it without reacting each component contained in the coating film-forming composition.

[0100] The composition can be applied directly to any substrate by any known application method such as spraying, brushing, roller, curtain flow, roll, dip, or coater.

[0101] During drying, each component in the coating film-forming composition may be partially or completely reacted. The coating film-forming composition may be applied to an adherend, dried, and then irradiated with light. After drying, the coating film-forming composition may be irradiated with light, and each component in the coating film-forming composition may be partially or completely reacted.

[0102] The drying temperature is, for example, from 30° C. to 150° C., and the drying time is, for example, from 1 minute to 1 hour. The light irradiation is preferably UV light irradiation, and the amount of irradiation light and the like are appropriately set depending on the area and thickness of the coating film.

[0103] Specific examples of the adherend include various structures such as metal products, wood products, plastic products, glass products, medical parts (e.g., catheters, stents, gloves, tweezers, containers, guides, trays, etc.), painting-related parts (e.g., robot arms, painting booths, hangers, covering materials, ovens, etc.), buildings (interior and exterior wall surfaces, floors, and ceiling surfaces), electronic devices, transportation equipment (e.g., automobiles, motorcycles, railway vehicles, and ships, etc.), and the structural members that make up these structures.

[0104] <Coated items> The coated article according to the embodiment of the present invention is provided with the above-mentioned coating film. The above-mentioned coating film-forming composition is applied to an adherend (article) and dried to obtain a coated article provided with a coating film. A coating film that is excellent in terms of ease of cleaning against adhered dirt can be obtained. The method of applying the coating film-forming composition and the adherend are as described above in the section on the coating film-forming composition.

[0105] As described above, the present specification discloses the following:

[0106] [1] (A) A coating film containing a resin, The (A) resin has at least two types of functional groups in its side chain, The coating film has a surface having a contact angle with water of 65° or less and a sliding angle of water of 60° or less. [2] The coating film according to [1], wherein the (A) resin has a crosslinked structure. [3] The coating film according to [1] or [2], wherein the functional groups of the (A) resin include a hydrophobic functional group and a hydrophilic functional group. [4] The coating film according to [3], wherein the content of the structural unit (a2-1) containing a hydrophobic functional group in the resin (A) is 10% by mass to 50% by mass. [5] The coating film according to [3], wherein the content of the structural unit (a1-1) containing a hydrophilic functional group in the resin (A) is 6% by mass to 50% by mass. [6] The coating film according to [3] or [4], wherein the hydrophobic functional group is at least one selected from a fluoro group, a fluorinated alkyl group, an alkyl group, and an alkylsilyl group. [7] The coating film according to [3] or [5], wherein the hydrophilic functional group is at least one selected from the group consisting of an alkoxy group, a hydroxy group, an amine group, a sulfone group, an amino group, an amide group, an imino group, a mercapto group, a hydrazino group, a carboxyl group, a sulfate ester group, a phosphate ester group, and a quaternary ammonium group. [8] A coating film-forming composition for forming the coating film according to any one of [1] to [7], (a) containing a resin component, The (a) resin component is a coating forming composition containing at least two kinds of resins each having a different functional group. [9] The coating forming composition according to [8], wherein the (a) resin component comprises a resin (a1) having a hydrophilic functional group in a side chain and a resin (a2) having a hydrophobic functional group in a side chain.

[10] The coating forming composition according to [9], wherein the resin (a1) and the resin (a2) are acrylic resins.

[11] The coating forming composition according to any one of [8] to

[10] , further comprising (b) a crosslinking agent.

[12] An article having the coating film according to any one of [1] to [7]. EXAMPLES

[0107] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following, "parts" means "parts by mass".

[0108] <Film forming properties> The coating film samples for measurement obtained in each of the Examples and Comparative Examples were evaluated for film-forming properties according to the following two-level scale. 〇: The coating surface has no tackiness and no abnormalities such as cracks Δ: The coating surface has a tacky feel, and no cracks are formed on the coating surface. ×: The coating surface has a tacky feel, and further cracks are generated on the coating surface. The results are shown in Tables 1 to 3.

[0109] <Contact angle> For the coating film samples for measurement obtained in each of the Examples and Comparative Examples, 2 μL of water was dropped onto the coating film surface, and the contact angle of the coating film surface after 5 minutes was measured using a contact angle meter (DropMaster, DM-701, manufactured by Kyowa Interface Science Co., Ltd.) by the sessile drop method according to JIS R 3257. The results are shown in Tables 1 to 3.

[0110] <Sliding angle> The sliding angle of the measurement coating samples obtained in each Example and Comparative Example was measured by the dynamic sliding method. 20 μL of water was dropped onto the coating surface of each measurement coating sample, and the sliding angle of the coating surface was measured by tilting the surface at 1° per second, and the angle (°) at which the water droplet moved was measured using a contact angle meter (DropMaster, DMo-501, manufactured by Kyowa Interface Science Co., Ltd.) and was taken as the sliding angle. The results are shown in Tables 1 to 3.

[0111] <Easy cleaning test for soot stains> The soot stain cleaning evaluation test was conducted according to JSTM J 7602:2003: Accelerated stain test method for building exterior wall materials. Specifically, 10 mg of carbon black (Orion Engineered Carbons, FW200), 45 mg of Kanto loam (APPIE JIS test 1 type 8), 135 mg of yellow ochre (Holbein Industrial PG230), and 10 mg of silica (APPIE JIS test powder 1 type 3) were added to 200 mL of water, and the mixture was stirred at 1000 rpm for 3 minutes using a homodisper, and then dispersed for 5 minutes using an ultrasonic cleaner to obtain a stained liquid. Next, the color difference of the coating sample for measurement was measured using a color difference meter (Konica Minolta, CR-20) and was taken as "initial hue" (L1, a1, b1). Then, 0.5 mL of the contaminant liquid was dropped onto the surface of the coating sample for measurement using a pipette, and the sample was dried overnight at room temperature. After about 20 seconds of applying tap water to the adhered stains, the water was drained and the sample was left to dry overnight at room temperature, and the hue of the same spot was then measured and taken as "post-cleaning hue" (L2, a2, b2). The "initial hue" and "post-cleaning hue" were compared, and the color difference ΔE was calculated using the formula below. ΔE={(ΔL * ) 2 +(Δa* ) 2 +(Δb * ) 2} 1 / 2 ΔL=L1-L2 Δa=a1-a2 Δb=b1-b2 In addition, L1, a1, and b1 mean the "initial hue," and L2, a2, and b2 mean the "post-wash hue."

[0112] [Easy cleaning of soot stains] The ease of cleaning soot stains was evaluated using the following three-level scale. ◎:ΔE≦10 ○:10<ΔE<15 ×:15≦ΔE The results are shown in Tables 1 to 3.

[0113] <Preparation of Coating Film-Forming Composition> Example 1 20 parts by weight of 1WX-1020, 3.4 parts by weight of Karenz MOI, and 0.01 parts by weight of OL-1 were placed in a 110 mL screw bottle and stirred at 500 rpm in a 50°C water bath using a magnetic stirrer for 4 hours, after which 80 parts by weight of 8FS-001, 0.05 parts by weight of Omnirad 184, and 0.05 parts by weight of Omnirad 651 were added and stirred again at 500 rpm in a 50°C water bath using a magnetic stirrer for 1 hour to obtain a coating composition.

[0114] The obtained coating composition was applied to the surface of a 75 μm-thick PET film (Lumirror S10#75, Toray Industries, Inc.) using an applicator (YBA type Baker applicator, Yoshimitsu Seiki Co., Ltd.) so that the wet thickness was 200 μm, and the film was heated in an oven at 80° C. for 1 hour to form a layer. A release sheet (Mitsubishi Chemical MRE38) was firmly attached to the surface of the layer using a roller, and the release sheet side was irradiated with a UV irradiator at an illuminance of 2.5 mW / cm. 2 The separator was then peeled off to obtain a coating sample for measurement.

[0115] (Examples 2 to 7) Coating forming compositions and measurement coating samples of Examples 2 to 7 were obtained in the same manner as in Example 1, except that the type and content of each component and the film-forming conditions were changed as shown in Table 1.

[0116] Example 8 30 parts by weight of 1WX-1020, 5.51 parts by weight of Coronate HXR, and 70 parts by weight of 8BS-9000 were placed in a 110 mL screw bottle and stirred at 500 rpm for 4 hours in a 50 degree water bath using a magnetic stirrer to obtain a coating forming composition.

[0117] The obtained coating composition was applied to the surface of a 75 μm thick PET film (Lumirror S10#75, Toray Industries, Inc.) using an applicator (YBA type Baker applicator, Yoshimitsu Seiki Co., Ltd.) so that the wet thickness was 200 μm, and the film was heated in an oven at 80°C for 1 hour to obtain a coating sample for measurement.

[0118] Example 9 A coating forming composition and a coating sample for measurement of Example 9 were obtained in the same manner as in Example 8, except that the content of each component was changed as shown in Table 1.

[0119] Example 10 30 parts by mass of 1WX-1020 and 70 parts by mass of 8FS-001 were placed in a 110 mL screw bottle and stirred at 500 rpm for 4 hours in a 50°C water bath using a magnetic stirrer to obtain a coating forming composition.

[0120] The obtained coating composition was applied to the surface of a 75 μm-thick PET film (Lumirror S10#75, Toray Industries, Inc.) using an applicator (YBA type Baker applicator, Yoshimitsu Seiki Co., Ltd.) so that the wet thickness was 200 μm, and the film was heated in an oven at 80° C. for 1 minute to form a layer. A release sheet (MRE38, Mitsubishi Chemical Corporation) was firmly attached to the surface of the layer using a roller, and the release sheet side was irradiated with a UV irradiator at an illuminance of 2.5 mW / cm. 2 The separator was then peeled off to obtain a coating sample for measurement.

[0121] Comparative Example 1 A coating forming composition and a coating sample for measurement of Comparative Example 1 were obtained in the same manner as in Example 10, except that the content of each component was changed as shown in Table 1.

[0122] Comparative Example 2 A coating forming composition and a coating sample for measurement of Comparative Example 2 were obtained in the same manner as in Example 1, except that the content of each component was changed as shown in Table 1.

[0123] Comparative Example 3 0.5 parts by mass of 1WX-1020, 0.3 parts by mass of Karenz MOI, and 0.05 g of OL-1 were placed in a 110 mL screw bottle and stirred using a magnetic stirrer in a 50°C water bath at 500 rpm for 4 hours, after which 0.5 parts by mass of 8FS-001, 0.2 parts by mass of Omnirad 184, 0.2 parts by mass of Omnirad 651, and 100 parts by mass of DPHA were added and stirred again using a magnetic stirrer in a 50°C water bath at 500 rpm for 1 hour to obtain a coating forming composition.

[0124] The obtained coating composition was applied to the surface of a 75 μm-thick PET film (Lumirror S10#75, Toray Industries, Inc.) using an applicator (YBA type Baker applicator, Yoshimitsu Seiki Co., Ltd.) so that the wet thickness was 200 μm, and the film was heated in an oven at 80°C for 1 hour to form a layer. A release sheet (Mitsubishi Chemical MRE38) was firmly attached to the surface of the layer using a roller, and the release sheet side was irradiated with a UV irradiator at an illuminance of 2.5 mW / cm. 2 The separator was then peeled off to obtain a coating sample for measurement.

[0125] Comparative Example 4 0.5 parts by mass of 8FS-001, 0.2 parts by mass of Omnirad 184, 0.2 parts by mass of Omnirad 651, 100 parts by mass of DPHA, and 2 parts by mass of 8WX-022A were placed in a 110 mL screw bottle and stirred at 500 rpm for 1 hour in a 50°C water bath using a magnetic stirrer to obtain a coating composition.

[0126] The obtained coating composition was applied to the surface of a 75 μm-thick PET film (Lumirror S10#75, Toray Industries, Inc.) using an applicator (YBA type Baker applicator, Yoshimitsu Seiki Co., Ltd.) so that the wet thickness was 200 μm, and the film was heated in an oven at 80°C for 30 minutes to form a layer. A release sheet (Mitsubishi Chemical MRE38) was firmly attached to the surface of the layer using a roller, and the release sheet side was irradiated with a UV irradiator at an illuminance of 2.5 mW / cm. 2 The separator was then peeled off to obtain a coating sample for measurement.

[0127] Comparative Example 5 A 110 mL screw bottle was charged with 16.5 parts by weight of 8FS-001, 0.2 parts by weight of Omnirad 184, 0.2 parts by weight of Omnirad 651, 23.5 parts by weight of DPHA, and 60 parts by weight of Light Acrylate 130A, and the mixture was stirred using a magnetic stirrer at 500 rpm in a 50°C water bath for 1 hour to obtain a coating composition.

[0128] The obtained coating composition was applied to the surface of a 75 μm-thick PET film (Lumirror S10#75, Toray Industries, Inc.) using an applicator (YBA type Baker applicator, Yoshimitsu Seiki Co., Ltd.) so that the wet thickness was 200 μm, and the film was heated in an oven at 80°C for 30 minutes to form a layer. A release sheet (Mitsubishi Chemical MRE38) was firmly attached to the surface of the layer using a roller, and the release sheet side was irradiated with a UV irradiator at an illuminance of 2.5 mW / cm. 2 The separator was then peeled off to obtain a coating sample for measurement.

[0129] Comparative Example 6 A coating forming composition and a coating sample for measurement of Comparative Example 6 were obtained in the same manner as in Comparative Example 5, except that the content of each component was changed as shown in Table 1.

[0130] The details of each component in Tables 1 to 3 are as follows. <Components containing hydrophobic resin (a2)> 8BS-9000: Silicone acrylic polymer, solid content 35%, manufactured by Taisei Fine Chemical Co., Ltd. 8FS-001: Fluorosilicone acrylic polymer, solid content 50%, manufactured by Taisei Fine Chemical Co., Ltd. 8FS-009: Fluorosilicone acrylic polymer, solid content 50%, manufactured by Taisei Fine Chemical Co., Ltd. <Component Containing Hydrophilic Resin (a1)> 1WX-1020: Quaternary ammonium salt acrylic polymer, solid content 39.5%, manufactured by Taisei Fine Chemical Co., Ltd. 8WX-022A: Quaternary ammonium salt acrylic polymer, solid content 40%, manufactured by Taisei Fine Chemical Co., Ltd. Light Acrylate 130A: PEG acrylic polymer, solid content 99%, manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Acrylate" <Crosslinking agent> Coronate HXR: Polyisocyanate, manufactured by Tosoh Corporation. Karenz MOI: Isocyanate-containing acrylic compound, manufactured by Resonac Co., Ltd., product name "Karenz" DPHA: Polyacrylate, manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD" <Catalyst> OL-1: Tin catalyst, manufactured by Tokyo Fine Chemical Co., Ltd., product name "Empiraizer OL-1" Omnirad 184: Photopolymerization initiator, manufactured by BASF Ltd. Omnirad 651: Photopolymerization initiator, manufactured by BASF Ltd.

[0131] In addition, in Tables 1 to 3, the amounts of structural units containing hydrophilic functional groups and structural units containing hydrophobic functional groups were calculated based on the catalog values ​​of the hydrophilic functional groups and hydrophobic functional groups of each resin component contained in the coating film-forming composition.

[0132] [Table 1]

[0133] [Table 2]

[0134] [Table 3]

[0135] As shown in Tables 1 to 3 above, the coating film-forming compositions of Examples 1 to 10 were found to have excellent soot-soiling cleanability because the contact angle of the coating film surface prepared using the composition was 65° or less and the sliding angle was 60° or less.

[0136] On the other hand, the coating film-forming compositions of Comparative Examples 1 to 6 had poor antifouling properties because the contact angle of the coating film surface produced using the composition exceeded 65° or the sliding angle exceeded 60°.

[0137] Although various embodiments have been described above with reference to the drawings, it goes without saying that the present invention is not limited to such examples. It is clear that a person skilled in the art can come up with various modified or revised examples within the scope of the claims, and it is understood that these also naturally belong to the technical scope of the present invention. Furthermore, the components in the above-mentioned embodiments may be arbitrarily combined within the scope of the invention. [Explanation of symbols]

[0138] 21 Coating 31 Adherent

Claims

1. (A) A coating film containing a resin, The resin (A) has at least two types of functional groups in a side chain, The coating film has a surface having a contact angle with water of 65° or less and a sliding angle of water of 60° or less.

2. The coating film according to claim 1 , wherein the resin (A) has a crosslinked structure.

3. The coating film according to claim 1 or 2, wherein the functional groups contained in the resin (A) include a hydrophobic functional group and a hydrophilic functional group.

4. The coating film according to claim 3, wherein the content of the structural unit (a2-1) containing a hydrophobic functional group in the resin (A) is 10% by mass to 50% by mass.

5. The coating film according to claim 3, wherein the content of the structural unit (a1-1) containing a hydrophilic functional group in the resin (A) is 6% by mass to 50% by mass.

6. The coating film according to claim 3 , wherein the hydrophobic functional group is at least one selected from the group consisting of a fluoro group, a fluorinated alkyl group, an alkyl group, and an alkylsilyl group.

7. 4. The coating film according to claim 3, wherein the hydrophilic functional group is at least one selected from the group consisting of an alkoxy group, a hydroxy group, an amine group, a sulfone group, an amino group, an amide group, an imino group, a mercapto group, a hydrazino group, a carboxyl group, a sulfate ester group, a phosphate ester group, and a quaternary ammonium group.

8. A coating film forming composition for forming the coating film according to claim 1, (a) containing a resin component, The coating film forming composition, wherein the resin component (a) contains at least two kinds of resins each having a different functional group.

9. 9. The coating forming composition according to claim 8, wherein the (a) resin component comprises a resin (a1) having a hydrophilic functional group in a side chain and a resin (a2) having a hydrophobic functional group in a side chain.

10. The coating forming composition according to claim 9 , wherein the resin (a1) and the resin (a2) are acrylic resins.

11. The coating forming composition according to any one of claims 8 to 10, further comprising (b) a crosslinking agent.

12. A coated article comprising the coating film according to claim 1 or 2.

Citation Information

Patent Citations

  • Surface conditioning agent for addition to coating film-forming liquid agent

    JP2021084924A